An Exploration of Some Antecedents and Consequences of Creative Self‐Efficacy among College Students. (23rd April 2016) - Puente‐Diaz, Rogelio; Cavazos‐Arroyo, Judith
Abstract: Two studies examined the role of task‐, self‐, and other‐approach achievement goals, trait curiosity, and enjoyment as antecedents of creative self‐efficacy and the influence of creative self‐efficacy on grade point average and perceived performance/effort exerted among college business students from Mexico. To test our research hypotheses, we used Structural Equation Modeling treating the variables as latent. Results from study 1 showed that task/self‐approach goal was a significant antecedent of creative self‐efficacy and enjoyment a marginally significant antecedent. Results from study 2 showed a positive, significant influence of trait curiosity on creative self‐efficacy. Similarly, creative self‐efficacy had a positive, direct influence on perceived performance/effort exerted and an indirect influence on students' grade point average. The implications of our results were discussed.